Clinical, functional and health-related quality of life correlates of clinically significant symptoms of anxiety and depression in patients with systemic sclerosis: a cross-sectional survey. - Christelle Nguyen; Brigitte Ranque; Thierry Baubet; Alice Bérezné; Caroline Mestre-Stanislas; François Rannou; Agathe Papelard; Sandrine Morell-Dubois; Michel Revel; Marie-Rose Moro; Loïc Guillevin; Serge Poiraudeau; et al. (PLoS ONE)
Objectives To identify clinical, functional and health-related quality of life (HRQoL) correlates of clinically significant symptoms of anxiety and depression in patients with systemic sclerosis (SSc). Methods Three-hundred-and-eighty-one patients fulfilling the American College of Rheumatology and/or the Leroy and Medsger criteria for SSc were assessed for visceral involvement, disability and HRQoL (assessed by SF-36). Clinically significant symptoms of anxiety and depression were evaluated with the Hospital Anxiety Depression Scale (HAD) (defined cut-off≥8). Results 9.2% the patients had limited SSc, 50.5% limited cutaneous SSc (lcSSc), and 40.3% diffuse cutaneous SSc (dcSSc). Overall, 40.4% and 58.8% of the patients had clinically significant symptoms of depression and anxiety, respectively. Compared to patients without clinically significant symptoms of depression, patients with clinically significant symptoms of depression had poorer health status, HRQoL mental and physical component, and greater global disability, hand disability and aesthetic impairment. Compared to patients without clinically significant symptoms of anxiety, patients with clinically significant symptoms of anxiety had poorer SF-36 mental and physical component scores. On multivariable analysis, excluding mental component score of SF-36, variables independently associated with clinically significant symptoms of depression and anxiety were global disability and physical component of SF-36, plus female gender for clinically significant symptoms of anxiety only. Remarkably, patients with and without clinically significant psychiatric symptoms were comparable for all disease-related clinical features assessed. Conclusion High levels of clinically significant symptoms of anxiety and depression are observed among SSc patients. Clinically significant psychiatric symptoms are rather associated with increased disability and altered HRQoL, than with disease-specific organ manifestations.